Modification of SOL profiles and fluctuations with line-average density and divertor flux expansion in TCV. (3rd August 2017) - Vianello, N.; Tsui, C.; Theiler, C.; Allan, S.; Boedo, J.; Labit, B.; Reimerdes, H.; Verhaegh, K.; Vijvers, W.A.J.; Walkden, N.; Costea, S.; Kovacic, J.; et al.
Abstract: A set of Ohmic density ramp experiments addressing the role of parallel connection length in modifying scrape off layer (SOL) properties has been performed on the TCV tokamak. The parallel connection length has been modified by varying the poloidal flux expansion f x . It will be shown that this modification does not influence neither the detachment density threshold, nor the development of a flat SOL density profile which instead depends strongly on the increase of the core line average density. The modification of the SOL upstream profile, with the appearance of what is generally called a density shoulder, has been related to the properties of filamentary blobs. Blob size increases with density, without any dependence on the parallel connection length both in the near and far SOL. The increase of the density decay length, corresponding to a profile flattening, has been related to the variation of the divertor normalized collisionality Λ d i v (Myra et al 2006 Phys. Plasmas 13 112502, Carralero et al, ASDEX Upgrade Team, JET Contributors and EUROfusion MST1 Team 2015 Phys. Rev. Let . 115 215002), showing that in TCV the increase of Λ d i v is not sufficient to guarantee the SOL upstream profile flattening.